Association between postoperative pain severity and oxygen saturation: a retrospective cross-sectional study in surgical patients - Ircham Saifudin; Widigdo Rekso Negoro; Annes Rindy Permana; Agus Budi Prasetyo; Muhammad Rodli; Sindu Sintara (International Journal of Public Health Science (IJPHS), 2026)
Postoperative pain is a common clinical problem that may compromise physiological stability and delay recovery, potentially reducing oxygenation, increasing infection risk, and prolonging hospitalization. This study aimed to examine the correlation between postoperative pain intensity and oxygen saturation levels. This study employed a quantitative correlational analytic design with a cross-sectional approach using retrospective medical record data. Data were collected at a single time point, with both postoperative pain intensity and oxygen saturation (SpO₂) measured simultaneously at approximately 12 hours after surgery when patients were clinically stable in the postoperative ward. A total of 208 eligible patients were included using total sampling. Data were analyzed descriptively and using the Chi-square test, with statistical significance set at p < 0.05. The results showed that 74% of patients experienced severe pain and 26% mild pain, while 49.5% presented with reduced oxygen saturation. A statistically significant association was identified between pain intensity and oxygen saturation (p < 0.001). Patients with low oxygen saturation were 25.5 times more likely to report severe pain (OR = 25.505; 95% CI: 6.379-101.979). In conclusion, postoperative pain intensity is significantly associated with oxygen saturation levels. These findings support the integration of subjective pain assessment with objective physiological monitoring, and future prospective studies are recommended to clarify causal relationships.